Strengthening the Basic Skills of Prospective Teachers of Islamic Religious Education through Integrated Field Practices at Sirojul Falah Islamic College - Azzahra, Siti Fatimah; Fitri, Anisa; Nurlaelah, Nurlaelah; Rismawati, Rismawati; Edy, Edy; Sofyan, Ahmad (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to explore strategies that can strengthen the core skills of future teachers of Islamic religious education through the Field Teacher Training Program (PLPK) at STAI Sirojul Falah. In the context of the ever-changing dynamics of education, the presence of strong pedagogical skills is essential for future teachers. This study used a qualitative method with downsizing data collection, data reporting, and interview insights to examine students' experiences during PLPK, as well as challenges they faced such as lack of direct experience and difficulties in managing the classroom. Interviews with students and supervisors have shown that thorough preparation and good support are key to increasing their competence. This study also found that the integration of theory and practice into the learning process is an important factor in the development of basic skills. In addition, character education is considered very important in the interaction between future teachers and students. The results of this study are expected to serve as recommendations for the development of educational programs at STAI Sirojul Falah and provide useful insights into future education policies. The results of the study show that PLPK contributes to the readiness of future teachers to solve problems in this area, as well as supports them in becoming competent and professional teachers.